Ultrasound Guidance for Renal Tract Access and Dilation Reduces Radiation Exposure during Percutaneous Nephrolithotomy - Thomas Chi; Selma Masic; Jianxing Li; Manint Usawachintachit (Advances in Urology)
Purposes. To present our series of 38 prone percutaneous nephrolithotomy procedures performed with renal access and tract dilation purely under ultrasound guidance and describe the benefits and challenges accompanying this approach. Methods. Thirty-eight consecutive patients presenting for percutaneous nephrolithotomy for renal stone removal were included in this prospective cohort study. Ultrasonographic imaging in the prone position was used to obtain percutaneous renal access and guide tract dilation. Fluoroscopic screening was used only for nephrostomy tube placement. Preoperative, intraoperative, and postoperative procedural and patient data were collected for analysis. Results. Mean age of patients was 52.7±17.2 years. Forty-five percent of patients were male with mean BMI of 26.1±7.3 and mean stone size of 27.2±17.6 millimeters. Renal puncture was performed successfully with ultrasonographic guidance in all cases with mean puncture time of 135.4±132.5 seconds. Mean dilation time was 11.5±3.8 min and mean stone fragmentation time was 37.5±29.0 min. Mean total operative time was 129.3±41.1. No patients experienced any significant immediate postoperative complication. All patients were rendered stone-free and no additional secondary procedures were required. Conclusions. Ultrasound guidance for renal access and tract dilation in prone percutaneous nephrolithotomy is a feasible and effective technique. It can be performed safely with significantly reduced fluoroscopic radiation exposure to the patient, surgeon, and intraoperative personnel.